2014
DOI: 10.1103/physrevb.90.144421
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic spiral induced by strong correlations inMnAu2

Abstract: The compound MnAu2 is one of the oldest known spin-spiral materials, yet the nature of the spiral state is still not clear. The spiral cannot be explained via relativistic effects due to the short pitch of the spiral and the weakness of the spin-orbit interaction in Mn, and another common mechanism, nesting, is ruled out as direct calculations show no features at the relevant wave vector. We propose that the spiral state is induced by a competition between the short-range antiferromagnetic exchange and a long-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
24
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 40 publications
6
24
1
Order By: Relevance
“…14 With the increase of Mn doping, T C increases from 20 K to 30 K, while M sat decreases from 2.17 µ B to 0.68 µ B , which probably reflect the competition between the short-range antiferromagnetic superexchange of nearest-neighbor (NN) Mn moments and a longer-range ferromagnetic interaction of distant Mn moments regulated by carriers, like the RKKY-like interaction. 4,36 The direct antiferromagnetic coupling between the Mn-Mn pairs causes antiferromagnetic order in LiMnAs with T N = 373.8 K. 37 Similar results were found in other previously reported DMSs. 11,17,18,20,25,35 We fixed Mn content at the level of 15%, and enhanced the doping levels of Co from 5% to 15%.…”
Section: Magnetic Propertiessupporting
confidence: 79%
“…14 With the increase of Mn doping, T C increases from 20 K to 30 K, while M sat decreases from 2.17 µ B to 0.68 µ B , which probably reflect the competition between the short-range antiferromagnetic superexchange of nearest-neighbor (NN) Mn moments and a longer-range ferromagnetic interaction of distant Mn moments regulated by carriers, like the RKKY-like interaction. 4,36 The direct antiferromagnetic coupling between the Mn-Mn pairs causes antiferromagnetic order in LiMnAs with T N = 373.8 K. 37 Similar results were found in other previously reported DMSs. 11,17,18,20,25,35 We fixed Mn content at the level of 15%, and enhanced the doping levels of Co from 5% to 15%.…”
Section: Magnetic Propertiessupporting
confidence: 79%
“…This method defines a wave vector q = (0, 0, q z ) that is applied to a primitive cell to simulate spirals. In our previous study of MnAu 2 [19], we found good agreement between the calculated energies obtained via this method and noncollinear calculations of spirals in supercells. In this study, our procedure was to calculate the energy as a function of the wave vector for the range 0 < q z < 2π/c as we varied the pressure, charge doping, and Hubbard U .…”
Section: Computational Detailsmentioning
confidence: 81%
“…The validity of applying this model to MnAu 2 was confirmed using density functional theory (DFT) calculations [18,19]. The origin of the magnetic frustration was traced to a competition between two exchange mechanisms, nearestneighbor superexchange and a transferred RKKY-like interaction, and electronic correlations were found to play an essential role in suppressing the RKKY-like interaction, which is necessary to satisfy the |J 1 | < 4|J 2 | inequality [19].…”
Section: Introductionmentioning
confidence: 92%
“…The ferromagnetic coupling in the Mn-Mn pair is attributed to a long-range p-d exchange interaction mediated by itinerant holes, which is shown in J. K. Glasbrenner, I.Žutić, and I. I. Mazin. 22 It compared with the experimental results from La 1-x Sr x Cu 0.925 Mn 0.075 SO (x=0.075,Tc=200K), 16 in which the Tc increases with the Sr doping level (x), proportional to the carrier density, indicating that the induction of hole-type charge carriers is crucial to the enhancement of FM order. We suggest the mechanism in (Y 0.75 Sr 0.25 ) (Cu 0.75 Mn 0.25 )SO is the same as in (Ba 1-x K x )(Zn 1-y Mn y ) 2 As 2 .…”
Section: A Study Of Ycusomentioning
confidence: 99%
“…19 Besides synthesizing samples, the research includes the investigation of properties by experimental measurements and theoretical calculations. [20][21][22][23][24] However, up to now there are only few articles about the first-principle study in the 122 phase of new DMS, and rarely on optical properties investigation. 25 In case of 1111 phase, LaCuSO is a wide band gap (3.1eV) p-type conductive oxysulfide semiconductor, 26 and it can become metallic with Sr doping.…”
Section: Introductionmentioning
confidence: 99%